Bluetooth antenna for metal‐cased smart jewellery. Issue 3 (1st February 2020) - Siddiqui, T.A.; Khanal, P.; Vähä‐Savo, L.; Lindvall, N.; Holopainen, J.; Viikari, V.
Abstract : This Letter presents a Bluetooth antenna for metal‐cased smart jewellery. The designed antenna is competent enough to operate in free space; moreover, antenna performance is investigated with cubical shape model which has the electrical properties similar to human body tissue. The measured prototype achieves 68% total efficiency in the free space and 27% total efficiency when measured with a cubical model in the Bluetooth frequency range of 2.4–2.48 GHz.